What Fuels Natural Killers? Metabolism and NK Cell Responses - Gardiner, Clair M.; Finlay, David K. (Frontiers in Immunology, 2017)
There is a growing appreciation that cellular metabolism is important in determining the course of lymphocyte responses. Additionally, changes in metabolic processes have been linked to dysfunctional lymphocyte functions in a number of different diseases. While most early studies of metabolic regulation of lymphocyte function focused on T lymphocytes, an understanding of how metabolic pathways impact upon NK cell responses is now starting to emerge. In this review article we will discuss how cellular metabolism influences lymphocyte function with a particular focus upon NK cells.